Synthesis of vector control systems by localization method - Kucher, E S; Popov, N S; Gryzunova, T V (Journal of physics. Conference series, 2019)
The paper presents a method for synthesis of a speed control system of induction motor drive and synthesis of output voltage control system for permanent magnet synchronous generator fed by three phase inverter with active rectifier. The mathematical model of a wind mill connected to the permanent magnet synchronous generator unit with output voltage control is considered. A structural and parametric synthesis of vector control systems can be implemented using a special localization method, which makes it possible to purposefully organize loops of slow and fast motions by establishing deep feedbacks. The developed localization method of control systems synthesis provides robust and stable operation of objects under study. The paper also examines difficulties in the differentiating filter designing. The approach of multimovement closed loops design is used to decompose the synthesis task. Deep feedbacks allow engineers to design control systems insensitive to disturbances and to compensate signal and parametric disturbances of control object. The proposed approach could be used for synthesis of wide range of nonlinear and unstable systems. The operability and robustness of proposed approach is discussed in this paper.